2019
DOI: 10.37859/jp.v9i2.1201
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi Dan Sifat Kemagnetan Pasir Besi Ekstraksi Asal Pantai Betaf Sarmi, Papua

Abstract: Characterization and magnetic behavior test of extracted iron sand from Betaf beach of Sarmi Papua was studied. The purpose of the recearch was to determine minerals content, phase of iron compound, and magnetic behavior of extracted iron sand from Betaf beach of Sarmi Papua were caculate using XRF, XRD and VSM. The result showed that extrated iron sand was contained 43,81% of Iron (Fe), 25,75% of Silika (Si) and 30,44 % others. The XRD pattern showed that the highest peak was magnetite (Fe3O4) at 2= 35,65o.  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, efforts are being made to obtain local iron sand in order to ensure the availability of magnetic minerals. The distribution of iron sand in various areas has been identified, including at Loji and Ciletuh Sukabumi beaches (Setiady et al, 2020), North Pringgabaya village, East Lombok (Safitri et al, 2020), Samas beach Bantul (Sismanto et al, 2017), Bubujung Tasikmalaya beach (Suwahyadi et al, 2021), Betaf Sarmi beach, Papua (Haryati et al, 2019), and iron sand in Sumbawa district (Nugraha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts are being made to obtain local iron sand in order to ensure the availability of magnetic minerals. The distribution of iron sand in various areas has been identified, including at Loji and Ciletuh Sukabumi beaches (Setiady et al, 2020), North Pringgabaya village, East Lombok (Safitri et al, 2020), Samas beach Bantul (Sismanto et al, 2017), Bubujung Tasikmalaya beach (Suwahyadi et al, 2021), Betaf Sarmi beach, Papua (Haryati et al, 2019), and iron sand in Sumbawa district (Nugraha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The iron sands in Papua have begun to attract attention nowadays, in particular on the north coast of Papua. Our previous studies focused on the iron sand from the coastal areas in Sarmi Regency [12][13][14][15]. The natural iron sand in Sarmi revealed that hematite and magnetite mineral were dominant [13], and they could be useful as a concrete raw material for nuclear protective walls [14].…”
Section: Introductionmentioning
confidence: 99%